Principal Leadership Strategies in Improving Teacher Performance Quality: A Case Study at MTs Maarif Ngalian, Wonosobo - Sukirman, Sukirman; Sukawi, Z; Muntaqo, Lutfan; Firdaus, Firdaus; Nadia, Silva (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2025)
This study aims to analyze the principal’s leadership strategies in improving teacher performance, identify the obstacles encountered in implementing these strategies, and explain how such challenges are addressed at MTs Ma’arif Ngalian, Wadaslintang District, Wonosobo Regency. The research employed a qualitative approach with a descriptive-analytical method. Data were collected through observation, interviews, and documentation, and analyzed through stages of planning, data collection, description, analysis, and conclusion drawing. The findings reveal that the principal enhances teacher performance by strengthening discipline, fostering work motivation, modeling exemplary leadership, and conducting academic supervision. The principal acts as an instructional leader who promotes continuous professional development. However, several challenges were identified, including low teacher discipline, limited motivation to improve performance, infrequent supervision, inadequate facilities and infrastructure, and the limited role of external supervisors. To address these obstacles, the principal reinforces disciplinary policies, promotes human resource development initiatives, conducts regular quarterly supervision, and coordinates with relevant stakeholders to improve physical and instructional facilities. These strategies contribute to strengthening teacher professionalism and improving overall educational quality.